The evaluation of health-related behaviours between the physically active and non-active women - Boguszewski, Dariusz; Adamczyk, Jakub Grzegorz; Kowalska, Sylwia; Sado-Drapała, Judyta; Lewandowska, Monika; Białoszewski, Dariusz (Polish Journal of Public Health, 2014)
Introduction. In the face of the more and more general threat with civilization diseases the promotion of healthy lifestyle should be one of main activities of educational and medical institutions. Aim. The aim of the work was comparison of chosen elements of healthy lifestyle between the young physically active women and non-sports ones. Material and methods. The survey was carried out on 156 women aged 18-35 years, divided into two groups. Persons physically active were classified into Group 1 (n=72), whereas into Group 2 – non-active ones (n=84). The investigative tool was the Inventory of Health-Related Behaviours by Juczyński (where health-related behaviours were rated in four categories: proper nutrition habits, prophylaxis behaviours, and positive attitude and health practices). Differences between the data were qualified with the t-student test for independent groups; level p≤0.05 was accepted as of minimum significance. Results. The results show that physically active persons pay greater attention to healthy lifestyle than non-sports people. The general indicator of health-related behaviours was noticeably higher in Group 1 (p=0.007). Greatest differences (p=0.008) were noted within the range of nutritional habits, and the least significant ones – in positive attitude (p=0.546). Conclusion. The positive influence of the physical activity on other aspects of the healthy lifestyle has been proven. It seems legitimate to promote physical activity among women of every age.